Use of the Dashboard as a Tool in the Management of Economic Entities: Array - Soare, Georgiana Janina (Acta Universitatis Danubius. Œconomica, 2021)
The dashboard is the tool that capitalizes on how to generate actions to improve the performance of the economic entity. The use of the dashboard as a tool in the management of economic entities is recommended in any analysis or managerial activity in which managers, based on information on the results obtained from the implementation of various activities, capitalize on the effectiveness of continuing economic activity under the same or other conditions.